(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Today eve on ‘March’ and a significant role played by media to expedite the rate of social change in society. The present paper highlights the role of media to raise the women issues and its impacts on the mindset of the people and the work as an agent of social change in the society. The different modes of media, including print and electronic media have been proved conducive to act as catalytic factor to expedite the process of planned change by raising the women relating issues like women’s atrocity, gender inequality, female foeticides, empowering the women, and equal right are some of the pressing issues which require a planned force to inculcate the right thing in to the wrong minds, living in different strata of society. It therefore, the different modes of media, including social media, citizen journalism and the new media have been playing a very significant role to stimulate all the changing parameters which are included to expedite the process of social change in terms of overcome the prejudices against the women on her work participation, acquiring the education, gender based discriminative behavior, equal wages, enjoying the constitutional and human rights and the support of media to bring a desirable changes in terms of overcome on steady growing gender based crimes against the women and the other pressing issues to air the views through different modes of media before the people. Lastly, there are some of the recommendations which is to be followed to cover these women issues; based on the authentic information; so that a desirable social change may come in the society.